Mindfulness Based Cognitive Theraphy: Lowering The Quarter Life Crisis in Achieving Happiness - Rina Rifayanti; Lisda Sofia; Siti Maisyah; Nadya Nurrahmah; Nurul Insani (Universitas Aisyah Pringsewu, 2022)
This study aims to determine whether there is a decrease in the behavior of the quarter-life crisis to achieve happiness after being given the Mindfulness-Based Cognitive Therapy method. Using a quantitative experimental approach and the research design used is Static Group Comparison. The aim is to measure the effectiveness of Mindfulness-Based Cognitive Therapy in this study to the experimental group. Subjects are 30 people who are experiencing a quarter-life crisis. The technique of data analysis is statistical analysis, namely Paired sample T-test. Salam's research shows: (1) There is a significant difference in the quarter-life crisis after being given Mindfulness-Based Cognitive Therapy with Paired Sample T-Test with p = 0.000 (p less than 0.05). (2) There is no significant difference in the quarter-life crisis on the subject before and before being given mindfulness-based cognitive therapy with the Paired Sample T-Test with a p-value = 0.741 (p more than 0.05).Abstrak: Penelitian ini bertujuan untuk mengetahui apakah terdapat penurunan perilaku quarter life crisis untuk mencapai kebahagiaan setelah diberikan metode Mindfulness Based Cognitive Theraphy. Desain penelitian yang digunakan adalah true experimental design. Tujuannya adalah untuk mengukur efektivitas Mindfullnes Based Cognitive Theraphy dari penelitian ini terhadap kelompok eksperimen. Subjek 30 orang yang sedang mengalami quarter life crisis. Teknik analisa data adalah analisis statistik yaitu Paired sampel T-test. Hasil penelitian menunjukkan: (1) Ada yang signifikan perbedaan quarter life crisis setelah diberikan Mindfulness Based Cognitive Theraphy dengan Paired Sample T-Test hasil nilai p = 0.000 (p kurang dari 0.05). (2) Tidak ada perbedaan yang signifikan quarter life crisis pada subjek sebelum dan sesudah tidak diberikan perlakuan mindfulness based cognitive therapy dengan Paired Sample T-Test hasil nilai p = 0.741 (p kurang dari 0.05).